Sequoyah, Cherokee hero - Oppenheim, Joanne; Dodson, Bert. (Mahwah, N.J. : Troll Associates, 1979)
A biography of the Cherokee Indian who invented a syllabary for the Cherokee language.
School Library Journal
4.0
3-6
Keywords: Sequoyah, -- 1770?-1843 -- Juvenile literature; Sequoyah, -- 1770?-1843.; Cherokee Indians -- Biography -- Juvenile literature; Cherokee Indians -- Writing -- Juvenile literature; Cherokee Indians -- Biography; Indians of North America -- Biography; Sequoyah, 1770?-1843.; Cherokee Indians -- Biography; Indians of North America -- Biography